Application of successful EU funds absorption models to sustainable regional development - Marko Šostar; Vladimir Ristanović; A. Chamaru De Alwis (Economies, 2023)
The research paper comprehensively and consistently addresses all relevant theoretical areas related to the topic and includes an extensive empirical analysis of the absorption of EU funds and their impact on the sustainable development of Croatia, Slovenia, Hungary, and Poland. The analysis aims to investigate the efficiency of the absorption of funds from the EU, the impact of these funds on regional development of countries, and the reasons for such impacts. The 'Regional Development Model Based on EU Funds' was tested with the aim of applying the model to the Republic of Croatia, countries in the region, and other European countries, to achieve a higher level of absorption of financial resources from the available EU funds. Data for the empirical analysis were collected using a highly structured survey questionnaire completed by a sample of 244 respondents involved in the preparation and implementation of EU-funded projects. The contribution of economic science in theoretical terms arises from the development of scientific knowledge and ideas about the importance of increasing the number of development projects that will increase the absorption of funds from the European Union, thereby increasing economic activities in Croatia and the region. The expected contribution of economic science in the applied sense is based on the formulation of the 'Regional Development Model Based on EU Funds', which is based on the application of knowledge, good practices, and stakeholder experiences, considering relevant indicators from available sources. The greatest contribution is demonstrated through testing the 'Regional Development Model Based on EU Funds', which is applicable to the Republic of Croatia, countries in the region, and other European countries over a longer period. Finally, research into the impact of EU funds on the regional development of recipient countries is considerably less represented and very modest, and is only in the 'upswing' of systematic scientific research. The research aims to fill the gaps in research and to encourage the thinking of key stakeholders responsible for regional development, who should eventually realize the importance of defining a regional policy aimed at EU funds as a key to regional development and reducing regional disparities within countries.
Keywords: 330; sustainable regional development; EU funds; development projects; absorption